Refinement of Gene Frequency Estimation Through an Iterative Approach in Genetic Data Analysis (International Journal of Food and Nutritional Sciences, 2021)
In genetic data analysis, accurate estimation of gene frequencies is of paramount importance for understanding the genetic composition of populations and their susceptibility to various traits and diseases. This paper presents an iterative procedure designed to enhance the precision of gene frequency estimation. The iterative approach involves initial gene frequency estimates, data collection, comparison of expected and observed data, and subsequent iterations to refine the estimates. By repeating this process until convergence, more reliable and accurate gene frequency estimates are obtained. Sensitivity analysis is also performed to assess the robustness of the final estimates. This iterative procedure serves as a valuable tool in the field of genetics, contributing to a deeper understanding of population genetics, heritability, and gene-environment interactions.